Pembimbingan Pribadi Religius Dalam Media Dakwah Ustadz Das’Ad Latif Untuk Mengembangkan Konsep Diri Siswa Smp Negeri 6 Parepare - Sakinah; Syamsuriadi; Supriadi; Taufiq Syam (Communication and Islamic Broadcasting Studies IAIN Parepare, 2022)
Islamic Broadcasting Communication Student IAIN Parepare is one of the study programs that uses Edlink as a distance learning medium. The use of edlink has started since the beginning of the odd semester of the 2020 academic year until now. Therefore, researchers are interested in researching the effectiveness of Edlink as a distance learning medium during the pandemic of Islamic Broadcasting Communications IAIN Parepare students. Overall, based on the results of the research which were then analyzed quantitatively, it is known that the effectiveness of using Edlink as a distance learning medium during the pandemic of Islamic Broadcasting Communication Students IAIN Parepare can be said to be quite effective. Most of the Islamic Broadcasting Communications Students of IAIN Parepare chose to use Edlink as a distance learning medium because of Edlink's ability to make it easier for students to receive or send assignments, the application is quite light, helps interaction between students and lecturers and the video conferencing feature where these things are not This can be done through other distance learning media. As for the things that hinder the effectiveness of Edlink as a distance learning medium, namely the problem of understanding the material, inadequate internet network, undisciplined lecture time, and the absence of facilities such as laptops.